Pengembangan Permainan Trading Card Augmented Reality Bertema Perang Baratayuda - Ramadhan Rizki Arga Putra; Wibisono Sukmo Wardhono; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Trading Card Game (TCG) is a popular card game that uses serial cards. But in this game, players can not really see the characters on the card in real form. It is necessary to develop TCG with the original concept but in a more interactive form by using 3D graphics to visualize the characters in the game. Games that lift the culture and wayang stories is one of another way to introduce Indonesian culture to the younger generation. Therefore, it is necessary to developed a Trading Card Game using Augmented Reality technology with Baratayuda War theme which will run on Android-based mobile devices. The method used in the development is Iterative with Rapid Prototyping (IRP) method. The IRP method can return to the previous process to make improvements. The story or scene chosen is Baratayuda Wars between Pandawa against Kurawa. The use of paper prototype on design makes it easy to set rules on this game. Based on the results of the implementation, the wayang objects can be integrated by using Augmented Reality to generate a real 3D effect inside the marker as a game card. For the creation of 3D objects is using Blender app and to display 3D wayang objects is using sdk vuforia in Unity game engine. Based on White Box testing and Black Box testing by applying independent path test on program based on Cyclomatix Complexity value, obtained validation test result that program can run well with 100% validation rate. In the playtesting that consisting of the element of fun and the element of ease of use, the results obtained that the game concept has been made quite interesting and quite easy played, but it's still too boring.